An experimental and computational analysis of combustion heat release transformation in dual fuel combustion. (1st June 2023) - Partridge, Kendyl R.; Jha, Prabhat R.; Srinivasan, Kalyan Kumar; Krishnan, Sundar Rajan
Highlights: Heat release profile shape changes with injection timing in dual fuel combustion. Heat release shape transformation accompanied by sharp NOx reduction. Unique analysis combining engine experimental and CFD results. Minimal impact of cylinder pressure and temperature on shape transformation. Local equivalence ratio stratification changes likely cause of shape transformation. Abstract: Dual fuel (DF) diesel-methane combustion, which employs a high-reactivity fuel (diesel) to ignite a low-reactivity fuel (methane), is a widely studied combustion strategy for internal combustion engines, with significant potential for engine-out emissions reductions without the need for major hardware modifications. A phenomenon, which has been reported in the DF literature, but not explained fully, is the transformation of the shape of the apparent heat release rate (AHRR) curve as the start of injection (SOI) of diesel is advanced beyond a certain threshold; coincidentally, this AHRR transformation is usually accompanied by a sharp decrease in engine-out emissions of oxides of nitrogen (NOx). The goal of the present work is to establish the underlying physical reason(s) that cause the AHRR transformation. The AHRR transformation was observed on a single cylinder research engine (SCRE) at an indicated mean effective pressure (IMEP) of 5 bar at a speed of 1500 rev/min. The transformation occurred over a range of SOIs from 330 to 320 crank angle degrees (CAD). While the 330 CAD SOI exhibited a typical two-stage AHRR curve, with a clearly definable first-stage peak followed by a second-stage AHRR with little-to-no low temperature heat release (LTHR) present and high engine-out NOx, the 320 CAD SOI exhibited a single-stage, Gaussian-like AHRR curve, with noticeable LTHR and at least one order-of-magnitude lower NOx emissions. Leveraging analysis of experimental data and three-dimensional computational fluid dynamic simulations, the authors show that the AHRR transformation is impacted mainly by differences in local equivalence ratio distributions within the cylinder at ignition onset for different diesel SOIs.